Pathology characteristics of Gastrointestinal Stromal Tumors (GIST) in Hue Central Hospital - Pham Nguyen Cuong; Nguyen Thanh Xuan, Pham Nhu Huy, Tran Xuan Tien, Nguyen Thi Hoai An (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Introduction: Gastrointestinal stromal tumors (GIST) are the most common mesenchymal neoplasms of the gastrointestinal system. The tumor arises from the middle layer of the gastrointestinal epithelium and can develop in organs such as the esophagus, stomach, small intestine, colorectal, or mesenteric. Histopathological examination is crucial in confirming GIST to choose appropriate therapeutics for patients. This study aims to explore the clinicopathological characteristics and evaluate the relationships between malignant risk classification according to Armed Forces Institute of Pathology criteria and the clinicopathological features of GISTs in a cohort of Vietnamese patients. Methods: Eighty-nine patients with primary GIST who underwent surgery with primary curative intent between 2014 and 2019 at Hue Central Hospital, Vietnam, were evaluated for clinicopathological characteristics and immunohistochemical findings. Results: The average age was 55.9 ± 11.9 years. Tumors > 2 - 5 cm accounted for 64.1%. The most common location was the stomach (48.5%). Rhomboid cell type was predominant (85.9%). All samples were positive for CD117, with Vimentin positive in 97.4%, and CD34 positive in 61.5%; no cases were positive for Desmin. High-risk GISTs dominated (46.9%), followed by intermediate risk (28.1%), low risk (20.2%), and very low risk (4.7%). Significant correlations were found between tumor necrosis and size, necrosis and the number of mitoses, and mucosal infiltration with tumor size. Conclusions: There is a significant association between the risk level according to AFIP criteria and the necrosis or mucosal invasion of the tumor.